MARKETING INVESTIGATION OF THE LIVESTOCK MARKET BY THE EXAMPLE OF IVANO-FRANKIVSK CITY - Perevozova , I.V.; Daliak , N.A. (The actual problems of regional economy development, 2017)
In the article are the resulted results of one marketing research are of types of small facilities of placing of hotel industry, namely hostels in town Ivano-Frankivsk. It is marked that hostel as an element of hotel business is an important aspect in development of economic activity, financial stimulation of city (on the example of Ivano-Frankivsk), update of sphere of economy, mobilizations of human capital which straight influences on development of internal tourism of every territorial subject. Modified need marketing research as a necessary theoretical and practical foundation of argumentation business ideas opening of hostel and forming a system of recommendations to improve its effectiveness in Ivano-Frankivsk.